2022
DOI: 10.1177/08997640211072852
|View full text |Cite
|
Sign up to set email alerts
|

The Hybridization of Meaningful Nonprofit Work: An Exploratory Study of the Effects of Marketization on Nonprofit Managers’ Sense of Meaningfulness in Work

Abstract: Nonprofit work is oftentimes viewed as inherently meaningful work, but the world of nonprofit work is changing by becoming increasingly marketized. These changes are impacting nonprofit workers’ conception and experience of meaningful work. Drawing from scholarship on neoliberal marketization, enterprise culture, and meaningful nonprofit work, this exploratory study examines how an increasingly marketized work environment is influencing nonprofit managers’ experience of meaningful work. Findings from interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For instance, commercial decisions of social enterprises (established as financial-capacity socialimpact builders) were affected by their founding nonprofit's mission (Fitzgerald & Shepherd, 2018); and meaningful nonprofit work reflected prosocial/market-values coexistence (B. Sandberg & Robichau, 2022). Furthermore, a scattering of embryonic research explores the performative effects of nonprofit motivations and life cycles.…”
Section: Sectoral Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, commercial decisions of social enterprises (established as financial-capacity socialimpact builders) were affected by their founding nonprofit's mission (Fitzgerald & Shepherd, 2018); and meaningful nonprofit work reflected prosocial/market-values coexistence (B. Sandberg & Robichau, 2022). Furthermore, a scattering of embryonic research explores the performative effects of nonprofit motivations and life cycles.…”
Section: Sectoral Motivationsmentioning
confidence: 99%
“…Conversely, studies have identified the trend of nonprofits toward embracing marketization/mission competing tensions to achieve growth and impact. For instance, commercial decisions of social enterprises (established as financial-capacity social-impact builders) were affected by their founding nonprofit’s mission (Fitzgerald & Shepherd, 2018); and meaningful nonprofit work reflected prosocial/market-values coexistence (B. Sandberg & Robichau, 2022).…”
Section: Innovation Performance and Governance Literaturementioning
confidence: 99%
“…Both role ambiguity and role conflict are role stressors that have been shown to be associated with emotional exhaustion, job dissatisfaction, and even burnout (Gilboa et al, 2008; Peiro et al, 2001; Rizzo et al, 1970; Schmidt et al, 2014). The article thus contributes to a stream of literature that discusses how the use of management practices originally developed for the business sector influences nonprofit organizations’ societal roles, the nature of the work they do, and the work-related perceptions and behavior of nonprofit staff, more particularly (e.g., Sandberg & Robichau, 2022; Suykens et al, 2023).…”
mentioning
confidence: 99%